2015
DOI: 10.17559/tv-20140326034118
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the knowledge management project at Croatian polytechnics

Abstract: Original scientific paperThe main aim of this paper was to establish to what extent the knowledge management project has become a reality at Croatian polytechnics, and how far polytechnics have fulfilled their task. The analysis was based on the perceptions of polytechnic students. In the survey encompassing 818 respondents the emphasis was on the assessment of knowledge gained, and the process of knowledge transfer. The research results have indicated that there are several areas in which additional efforts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Pisitsankkhakarn and Vassanadumrongdee [24] obtained from a survey analysis of 200 owners in Bangkok that product and price incentives can significantly increase consumers' purchase intention for remanufactured products. In terms of waste management, Tomasic et al [9] conducted questionnaires and interviews with the heads of leading brands of cars after sales in Croatia and found that they believe that more resources should be invested in customer awareness and staff education in order to better manage recycled parts. While the main barrier to the adoption of product return management among Malaysian car manufacturers investigated by Zailani et al [17] was closely related to the availability of resources to support product return activities.…”
Section: A Analyzing the Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Pisitsankkhakarn and Vassanadumrongdee [24] obtained from a survey analysis of 200 owners in Bangkok that product and price incentives can significantly increase consumers' purchase intention for remanufactured products. In terms of waste management, Tomasic et al [9] conducted questionnaires and interviews with the heads of leading brands of cars after sales in Croatia and found that they believe that more resources should be invested in customer awareness and staff education in order to better manage recycled parts. While the main barrier to the adoption of product return management among Malaysian car manufacturers investigated by Zailani et al [17] was closely related to the availability of resources to support product return activities.…”
Section: A Analyzing the Surveysmentioning
confidence: 99%
“…Future researchers can consider environmental and social impacts when studying reverse logistics barrier factors. In papers considering product waste management, Tomasic [9] and Zailani [17] analyzed the perspective of retailers and manufacturers, respectively, and future research scholars can analyze the perspective of other firms in the supply chain network, such as suppliers and logistics companies for product return management.…”
Section: Analysis Of Research Gap and Future Opportunitiesmentioning
confidence: 99%
“…The use of the Likert scale method -common during data collection -is found to be amenable to KM assessment. It captures the dimensions of interviewee perception about KM factors, which are precursors to KM performance (Armaghan & Renaud, 2017;Chawla & Saxena, 2016;Chen & Fong, 2015;Dukić, Kozina & Milković, 2015). Fuzzy methods have also been used in KM assessments, usually in factor validation, decision making processes, and performance improvement (Hesamamiri, Mahdavi Mazdeh, Jafari & Shahanaghi, 2015;Wang, Ding, Liu & Li, 2015;Lin, Chang & Lin, 2011).…”
Section: Knowledge-based Integrated Production Managementmentioning
confidence: 99%
“…Therefore, the management of such processes is system-oriented and their knowledge management approach is more likely to be explicit-oriented [13][14][15][16]. This is because non-routine processes are less predictable and documentable and their implementation is more based on the expertise and experience of people [17].…”
Section: Analysis Of Organization's Knowledge Approachesmentioning
confidence: 99%